Effects of dietary Lycium ruthenicum (black goji berry) branches supplementation on growth performance, meat quality, and muscle amino acid and fatty acid composition in sheep - Ma, Yan; Yang, Yuxia; Hou, Liangzhong; Li, Jinlong; Duan, Pingping; Guo, Tongjun (Frontiers in Veterinary Science, 2025)
IntroductionThe aim of this study was to investigate the effect of a preparation of black goji berry branches (Lycium ruthenicum) on growth performance, meat quality, amino acid and fatty acid content of sheep.MethodsThe experiment was a one-way completely randomized trial, in which 40 male sheep of the F1 generation of Dupo × Lake sheep crosses at four months of age were randomly divided into four groups of ten lambs each. Each group was fed an isoenergetic and isonitrogenous total mixed pellet ration containing 0% (CON), 10% (H1), 20% (H2) and 30% (H3) of Lycium ruthenicum branches. The experimental period included a pre-test adaptation of 10 d and an experimental test period of 60 d.ResultsThe Luminosity of each experimental group was highly significantly higher than that of the CON (p < 0.01). The values for Redness of the H2 and H3 groups were significantly higher than that of the CON (p < 0.05). The gamma-aminobutyric acid (GABA) concentration in the longest back muscle first increased and then decreased (p < 0.01), and the H2 group was extremely significantly higher than the CON and the other experimental groups. The H1 and H2 groups were significantly lower than the control group, decreasing by 6.87% and 7.07%, respectively (p < 0.05). The c20:0, c20:1 content showed a linear increase with increasing addition of Lycium ruthenicum, but the difference was not significant (p > 0.05).DiscussionThus, dietary feed supplementation with 20% of dried, ground Lycium ruthenicum branches can improve sheep meat quality and culture benefit.